Comparative Study of HTML and Animated User Interfaces of an Online Exhibition - Viralingam, Nagarajan; Ramaiah, Chennupati K. (DESIDOC Journal of Library & Information Technology, 2010)
The advancements in computer and telecommunication technologies have made the World Wide Web a vibrant place. Museums worldwide have recognised this phenomenon and are tapping the multimedia and interface technologies to present their contents online and in a more interesting manner. First priority to this is the user interface design and appropriate technologies to represent the contents. The paper discusses an animated interface created for an online exhibition with the Macromedia Flash software and compared the same with HTML user interface. The system evaluation results shows that only less than half of the users were satisfied with the animated version because of its inflexibility in terms of reusing and customising of information. Therefore, a HTML version was developed for the same system and compared for strengths and weaknesses in terms of user interfaces. The results showed that the respondents, especially those with lower bandwidth connections, were very comfortable with the HTML interface but aesthetically a few more percentage of respondents rated high to animated interface. The paper conclude that a balanced combination of HTML and animated interfaces will provide both aesthetics and functionality required for an online exhibition. DOI: 10.14429/djlit.28.4.196